POLITEKNIK DAN EKOWISATA BERKELANJUTAN : STUDI KOLABORASI POLINEMA-POLIWANGI DAN MITRA INTERNASIONAL - Alvin Nouval; Hilda Cahyani; Trias Rahardianto; Ratih Indri Hapsari (P3M Politeknik Negeri Malang, 2026)
The purpose of this community service program is to enhance awareness and knowledge of biodiversity and geoecotourism in Banyuwangi through experiential learning. By engaging youth participants from diverse backgrounds, the program provides hands-on experiences in local environmental conservation efforts, including coral reef restoration and sustainable farming practices. Using experiential learning as the primary approach, the program allows participants to directly interact with the community and natural environment, ensuring that theoretical knowledge is applied in real-life contexts. The results of this program show that participants gained valuable insights into sustainable practices and contributed to the preservation of local ecosystems. Furthermore, the program emphasized the role of green technologies and design thinking in addressing environmental challenges, leaving a positive impact on both the participants and the local community. The success of the program highlights the effectiveness of combining academic knowledge with practical engagement to foster sustainable development.